Ingestão Oral e Grau de Comprometimento da Disfagia Orofaríngea Neurogênica Pré e Pós-Fonoterapia - Pinto, Aline Rodrigues [UNESP]; Cola, Paula Cola; Carvalho, Lidia Raquel de [UNESP]; Motonaga, Suely Mayimi [UNESP]; Silva, Roberta Gonçalves da [UNESP] (Universidade Federal de Sao Paulo, 2014)
Objective. To compare, pre- and post-swallowing therapy, the level of oral intake scale, and the degree of severity of neurogenic oropharyngeal dysphagia. Method. 19 patients with oropharyngeal dysphagia: 10 Post-Stroke adults, aged from 44 years to 76 years (group 1 – G1), and nine children with Cerebral Palsy, aged from two years and five months to 15 years (group 2 – G2). We excluded individuals in the process of spontaneous recovery. We held retrospective analysis of clinical protocols for clinical speech therapy evaluation with classification of the degree of dysphagia severity, applied before and after swallowing therapy. We used the Functional Oral Intake Scale - FOIS to assess the level of oral ingestion, pre and post-swallowing therapy. Results. The degree of commitment of dysphagia was favorable change only in adults, and in FOIS these changes occurred in both groups. Conclusion. There were favorable changes in the degree of impairment of oropharyngeal dysphagia and levels of FOIS, pre and post - speech therapy in stroke, but in ECINP markers used showed no favorable changes should even be reviewed for application in this population. Future studies are needed to investigate the variables in this sample.

Objetivo. Comparar o nível de ingestão oral e o grau de comprometimento da disfagia orofaríngea neurogênica pré e pós - fonoterapia. Método. 19 indivíduos com disfagia orofaríngea neurogênica, 10 adultos pós-Acidente Vascular Cerebral (AVC), faixa etária de 4 a 76 anos, que compunham o grupo 1 (G1) e nove crianças com Encefalopatia Crônica Infantil Não Progressiva (ECINP), faixa etária de dois anos e cinco meses a 15 anos que compunham o grupo 2 (G2). Foram excluídos os adultos em fase de recuperação espontânea. Realizada aná- lise retrospectiva dos protocolos de avaliação fonoaudiológica clínica com classificação do grau de comprometimento da disfagia, aplicados pré e pós - fonoterapia. Foi utilizado o Functional Oral Intake Scale – FOIS para avaliar o nível de ingestão oral, pré e pós-fonoterapia. Resultados. Quanto ao grau de comprometimento das disfagias houve mudança favorável somente nos adultos, sendo que na FOIS estas mudanças ocorreram nos dois grupos. Conclusão. Houve mudanças favoráveis no grau de comprometimento da disfagia orofaríngea e nos níveis da FOIS, pré e pós – fonoterapia no AVC, porém na ECINP os marcadores utilizados não apresentaram mudanças favoráveis devendo inclusive ser revistos para aplicação nesta população. Serão necessários estudos futuros que investiguem as variáveis desta amostra.
Oral Intake and Severity Scale In Neurogenic Oropharyngeal Dysphagia
Keywords: disfagia